DK Eyewitness Travel Japan - Benson, John (Dk Pub, 2015)
A region-by-region travel guide to Japan that covers the country's history, culture, and landscapes and provides color photos, cutaway illustrations of architecture, maps, practical information, and details on sights to see, things to do, lodgings, and restaurants